2013
DOI: 10.14207/ejsd.2013.v2n1p171
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Eco-innovations to Leverage Sustainable Development of Eco-industry and Green Growth

Abstract: In the modern world, ecology and the economy are on cross roads. With the increasing pace of globalization and economic liberalization, giving birth to the rapid growth of consumerism by the modern civilization, there is growing consciousness to move gradually towards green growth with sustainability. This is now becoming possible by enhancing eco-consciousness both among the producers as well as the consumers. The chosen path is obviously to go in for more and more eco-innovations to provide complementarily t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 36 publications
1
24
0
5
Order By: Relevance
“…Companies keep on doing business assuming and applying environmental commitment in various ways. Over the last few years, environmental proactivity has become a goal for many companies (Aragón- Correa & Rubio-López, 2007;Rivera-Torres et al, 2015;Sharma, 2001), with different implementing manners tagged as green economy, circular economy (Witjes & Lozano, 2016) or eco-innovation (Garcés Ayerbe et al, 2016; Sarkar, 2013;Valero-Gil et al, 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Companies keep on doing business assuming and applying environmental commitment in various ways. Over the last few years, environmental proactivity has become a goal for many companies (Aragón- Correa & Rubio-López, 2007;Rivera-Torres et al, 2015;Sharma, 2001), with different implementing manners tagged as green economy, circular economy (Witjes & Lozano, 2016) or eco-innovation (Garcés Ayerbe et al, 2016; Sarkar, 2013;Valero-Gil et al, 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Arnkil et al (2010) showed the importance of supporting innovation by regional authorities. Sarkar (2013) proved that innovation stimulates sustainable development of the environmental sector and promotes green economic growth at all levels. Sotnyk et al (2013) investigated the influence of innovative information and communication technologies for achieving sustainable development of the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainable development (SD) is a multi-faceted idea, enveloping the interdependence of economic, social and ecological order in socio-economic development, and the necessity of preserving scarce resources for upcoming generations (Kates et al, 2005). Eco-innovation constitutes one of the solutions facilitating the implementation of the concept of SD (Sarkar, 2013;Dahan & Yusof, 2020). In general, one can identify three groups of definitions of ecoinnovation: 1) definitions related to sustainable development -in general -or related strictly to the environmental aspect (eco-innovation as an instrument); 2) definitions that focus on the life cycle of eco-innovation (eco-innovation as a process); 3) definitions that pertain to environmental gains and/or economic gains (eco-innovation as a source of effects).…”
Section: Significance Of Eco-innovations For Sustainable Developmentmentioning
confidence: 99%